Versatile Dibenzothio[seleno]phenes via Hexadehydro-Diels–Alder Domino Cyclization - Liu, Baohua; Hu, Qiong; Wen, Yinshan; Fang, Bo; Xu, Xiaoliang; Hu, Yimin (Frontiers in Chemistry, 2019)
A facile strategy to synthesize highly substituted dibenzoselenophenes and dibenzothiophenes by domino hexadehydro-Diels–Alder reaction is reported. The formation of three new C–C bonds, one new Caryl–Se/ Caryl–S bond, and a C–H -bond migration via one-pot multiterminal cycloaddition reactions were involved in over three transformations. The target tetracyclic compounds were prepared from tetraynes with a triphenylphosphine selenide or triphenylphosphine sulfide. This reaction played a pivotal role in constructing the natural thio[seleno]phene cores, which were highly substituted and is a robust method for producing fused heterocycles.